2016
DOI: 10.19053/0121053x.4217
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teaching in Rural Areas: A New Challenge for English Language Teachers in Colombia

Abstract: * Artículo de reflexión que da cuenta de algunos de los resultados del proyecto de investigación: "Towards the Exploration of Pre service Teachers Identities as Language Learners and Future Teachers: a Case Study", código SGI 1521,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 9 publications
0
17
0
3
Order By: Relevance
“…Despite the establishment of the English language in the form of linguistic imperialism, the learning of English constitutes a major curricular change in countries that see in this language a benefit for international interaction and economic growth (Woodend et al, 2019). Nonetheless, in many parts of the world, the teaching of English and the attainment of the L2 curricular goals in public elementary and secondary schools face many challenges (Coelho & Henze, 2014;Giannikas, 2011;Izquierdo et al, 2016;Lightbown & Spada, 2020;Ramos Holguín & Aguirre Morales, 2016;Roldán & Peláez, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the establishment of the English language in the form of linguistic imperialism, the learning of English constitutes a major curricular change in countries that see in this language a benefit for international interaction and economic growth (Woodend et al, 2019). Nonetheless, in many parts of the world, the teaching of English and the attainment of the L2 curricular goals in public elementary and secondary schools face many challenges (Coelho & Henze, 2014;Giannikas, 2011;Izquierdo et al, 2016;Lightbown & Spada, 2020;Ramos Holguín & Aguirre Morales, 2016;Roldán & Peláez, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selain itu, lingkungan keluarga atau orang tua dan tempat tinggal juga sangat berperan dalam membantu meningkatkan kualitas belajar siswa. Namun, peran orang tua di lingkungan pedesaan dalam membantu siswa belajar bahasa Inggris dinilai sangat rendah (Holguín & Morales, 2016).…”
Section: B Pengaruh Lingkunganunclassified
“…Ini menjadi salah satu bukti bahwa fasilitas sekolah sangat membantu terlaksananya proses pembelajaran di kelas. Jika fasilitas pembelajaran tidak memadai, maka proses pembelajaran bisa terhambat (Holguín & Morales, 2016).…”
Section: Kompetensi Guru Bahasa Inggrisunclassified
See 1 more Smart Citation
“…The concern over rural students' low achievement in the subject has been discussed quite extensively in the literature (Azman, 2011;Ee, 2012;Hassan & Rasiah, 2011;Nur, 2015;Wreikat, Kabilan, & Abdullah, 2014). Findings from several studies have shown that this phenomenon is more apparent in developing countries such as Tanzania (Mosha, 2014), Colombia (Holguín & Morales, 2016) and Bangladesh (Hossain, 2016). In the Malaysian context, the World Bank's (2010) report has provided alarming evidence of the disparity between urban and rural schools which is seriously pressing students' achievement in the subject, and this situation is the most serious and remains a prominent issue in poorer states such as Sabah, Kelantan, and Malacca.…”
Section: Introductionmentioning
confidence: 99%